2018
DOI: 10.3390/ijms19030674
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics in Osteoarthritis Based on an Understanding of Its Molecular Pathogenesis

Abstract: Osteoarthritis (OA) is the most prevalent joint disease in older people and is characterized by the progressive destruction of articular cartilage, synovial inflammation, changes in subchondral bone and peri-articular muscle, and pain. Because our understanding of the aetiopathogenesis of OA remains incomplete, we haven’t discovered a cure for OA yet. This review appraises novel therapeutics based on recent progress in our understanding of the molecular pathogenesis of OA, including pro-inflammatory and pro-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 114 publications
2
71
0
6
Order By: Relevance
“…The pathology of KOA is complex and involves numerous factors, including genetic predisposition (14,15), altered mechanical loading (16) and inflammation (17). Although the key processes leading to OA remain unclear, the death of chondrocytes and the loss of extracellular matrix are considered to be important features of the degeneration of articular cartilage in OA (18).…”
Section: Introductionmentioning
confidence: 99%
“…The pathology of KOA is complex and involves numerous factors, including genetic predisposition (14,15), altered mechanical loading (16) and inflammation (17). Although the key processes leading to OA remain unclear, the death of chondrocytes and the loss of extracellular matrix are considered to be important features of the degeneration of articular cartilage in OA (18).…”
Section: Introductionmentioning
confidence: 99%
“…But, beyond proteoglycan′s viscoelasticity, little is known about its other functions. In OA, the ECM containing proteoglycan is decreased [ 42 ], and abnormalities in endochondral ossification, as well as reduction in viscoelasticity, have been reported [ 16 ]. Therefore, in this study, we applied sPG to cells at multiple stages of endochondral ossification to investigate possible novel cartilage regulatory functions for proteoglycan, which goes beyond its role in cartilage viscoelasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Module analysis demonstrated that the development of OA synovitis is associated with ‘cytokine-cytokine receptor interactions’, ‘NOD-like receptor signaling pathway’, ‘Toll-like receptor signaling pathway’. Previous studies have demonstrated that the occurrence and development of OA were associated with a number of cytokines, leading to synovial inflammation, cartilage damage and osteophyte production ( 30 , 49 ). The present study demonstrated that OA synovial inflammation is associated with ‘NOD-like receptor signaling pathway’, ‘Toll-like receptor signaling pathway’ and ‘TNF signaling pathway’, and OA progression is additionally associated with ‘osteoclast differentiation’.…”
Section: Discussionmentioning
confidence: 99%